2022
DOI: 10.1049/cth2.12305
|View full text |Cite
|
Sign up to set email alerts
|

Distributed finite‐time formation control of multiple Euler–Lagrange systems under directed graphs

Abstract: This paper investigates the finite‐time formation problem of multiple Euler–Lagrange systems subject to model uncertainties and external disturbances under directed graphs. An adaptive distributed control approach is developed by integrating dynamic gain control and adaptive control based on the consensus theory and the finite‐time stability theory. Auxiliary scalar dynamics are constructed to facilitate dynamic gain design. It is shown that finite‐time formation can be achieved via the proposed non‐smooth con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The belief degree of each assessment grade in each rule is assigned based on empirical knowledge, as shown in Table 5. The antecedent attribute weight δ 11 f , f = 1, 2, and the rule weight θ 11 k , k = 1, . .…”
Section: Performance Assessment Model Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…The belief degree of each assessment grade in each rule is assigned based on empirical knowledge, as shown in Table 5. The antecedent attribute weight δ 11 f , f = 1, 2, and the rule weight θ 11 k , k = 1, . .…”
Section: Performance Assessment Model Constructionmentioning
confidence: 99%
“…Formation control for multi-UAVs refers to the fact that a group of UAVs can form and maintain a specific geometry in order to collaboratively accomplish a series of goals and can adapt to changes in the external environment by adjusting the geometry [9][10][11]. In general, formation control can be divided into three phases: the initial formation phase, the formation maintenance phase, and the formation reconfiguration phase-the last phase has the most complexity and challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such advantages have led to receiving a great deal of attention during the past years. Some impressive and important research has been reported on the finite-time control of various classes of dynamical systems such as multi-agent systems, switch systems, time-delay systems, stochastic systems, MIMO systems, and systems with input nonlinearities [6][7][8][9][10]. These studies have led to the achievement of valuable results in the control of different dynamical systems.…”
Section: Introductionmentioning
confidence: 99%